Seroprevalence and Risk Factors of Toxoplasma gondii in Wild Birds of Punjab Province, Pakistan - Naveed, Ahmad; Ali, Shahzad; Ahmed, Haroon; Simsek, Sami; Rizwan, Muhammad; Kaleem, Imdad; Umar, Sajid (Wildlife Disease Assoc, Inc, 2019)
Toxoplasma gondii is a protozoan parasite of veterinary and human public health importance for which birds act as an intermediate host. No information is available about the epidemiology of T. gondii in wild birds of Pakistan. The present study was designed to determine the seroprevalence and risk factors associated with T. gondii antibodies in wild birds of District Kasur, Punjab Province, Pakistan. A total of 200 wild birds of 28 species were captured from four tehsils (administrative subdistricts of districts) of the district Kasur and their serum samples screened for the presence of T. gondii antibodies using a latex agglutination test (cut-off value: 1:64). Twenty-five (13%) individual birds and 13 (46%) of the bird species were seropositive for T. gondii antibodies. There were statistical differences in T. gondii prevalence between adults and young (15% and 7%, respectively, P = 0.001) and healthy and sick (11% and 50%, respectively, P = 0.000) while there were not differences between genders, sites, urbanicity, and tehsils. The present study provides evidence of T. gondii antibodies in wild birds of Pakistan.
Keywords: Pakistan; seroprevalence; Toxoplasma gondii; wild birds